Makroekonomiczne znaczenie rozwoju handlu zagranicznego i jego wpływ na transformacje systemów gospodarczych średnio i nisko rozwiniętych (na przykładzie Polski) - Ćwikliński, Krzysztof (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The author discusses about economic meaning of foreign trading and tries to prove that this is a crucial meaning for countries in transformation state. Many important questions were asked, for example: Which countries are high, average and low developed? Does international trading influence growing of GDP and other economic variables? What is the meaning of external trading for average and low economies? What is the meaning of progressing international trading to the world economy and what are the problems involved with it? The author tries to understand and explain how international trading can accelerate the GDP. He would like to know the answer to the following question: what is the power of connections between foreign direct investments and import or export. The author applies well known (for economists) logical, statistic and econometric methods to solve problems and to give right answers for all questions. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 82-92